Living in a Modern City: Digital Practices of Homeless People in St Petersburg - A. S. Chernoivanova (Дискурс)
Introduction. The article describes the impact of the global trend of digitalization on the most vulnerable category of the population. The study of the digital divide is a fairly new area of research in the social sciences. Modern technologies are a part of our lives that influence social processes – in particular, it can increase or reduce social inequality. Modern researchers are finding more and more evidence of the growth of relative inequalities in Internet skills and Internet use. In case if the typical user’s “set” is a smartphone, the Internet and a laptop (or computer), the homeless person’s “set of technologies” may be different or not at all. Studies of the digital divide have already been conducted in large cities of socially and economically developed countries.Methodology and sources. The object of the study is a group with a low socio-economic status, homeless people, including those who have returned from prison. The study involved 15 respondents from 24 living in the social center at the time of the interview.Results and discussion. As a result of the analysis of the collected data, some features of the perception of digital technologies and practices of their use were identified. The peculiarities of perception are combined into a group of discursive patterns, the practice of using digital technologies – into a group of behavioral patterns. A good result of sociological research is the refutation of stereotypes that have developed in society. So, it seems possible to identify two main stereotypes. It is believed that mostly the homeless do not have cell phones, but if they do, it is likely a status thing for them. The second stereotype is associated with the repertoire of digital technologies: homeless people likely use non-personalized technologies due to their marginal position. Both stereotypes have been refuted. The unexpected result of the study indicates its absolute relevance and the prospect of further study, including vulnerable groups of the population.Conclusion. The prospect of future research is the continuation of the study on the example of other organizations and the study of other categories of homeless people (applying for overnight accommodation for one night or not visiting social organizations). It also should be noted, that the possibility of developing new social work practices taking into account the results of the study.